Effects of Key Financial Markets’ Infrastructure on Cash and Liquidity Management of Banks in India - Maiti, Sasanka Sekhar; Hemachandra, N. (Arthshastra Indian Journal of Economics & Research, 2018)
The article examined the effect of introduction of the Real Time Gross Settlement System (RTGS) on banks' cash requirements (viz. cash with banks) and liquidity requirements of banks (banker deposits) with the RBI. The empirical results indicated that the introduction of the RTGS system reduced cash requirements of banks significantly due to adoption of centralized processing systems, which facilitated better cash management for banks. However, at the same time, liquidity requirements of banks with the RBI increased on introduction of the RTGS, which did not grow with time, though more amount was settled in the RTGS. Demonetization resulted in huge cash requirements for banks, but it did not impact liquidity requirements of banks with the RBI.